Tuo-Min-Ding-Chuan Decoction Alleviate Ovalbumin-Induced Allergic Asthma by Inhibiting Mast Cell Degranulation and Down-Regulating the Differential Expression Proteins - Qin, Jingbo; Lv, Mingsheng; Jiang, Zeqiang; Meng, Xianghe; Wang, Yi; Cui, Jiarui; Wang, Ji; Wang, Qi (Frontiers in Pharmacology, 2021)
Allergic asthma is a stubborn chronic inflammatory disease, and is considered a co-result of various immune cells, especially mast cells, eosinophils and T lymphocytes. At present, the treatment methods of allergic asthma are limited and the side effects are obvious. Traditional Chinese medicine has been used to treat diseases for thousands of years in China. One such example is the treatment of allergic asthma, which take the characteristics of less adverse reactions and obvious curative effect. Tuo-Min-Ding-Chuan Decoction (TMDCD) is a traditional Chinese medicine compound for the treatment of allergic asthma optimized from Ma-Xing-Gan-Shi Decoction (MXGSD), which was put forward in Treatise on Febrile Diseases by Zhang Zhongjing in the Eastern Han Dynasty. The compound shows a significant clinical effect, but the mechanism of its influence on the immune system is still unclear. The purpose of this study was to observe whether TMDCD could alleviate the symptoms of ovalbumin (OVA) challenged allergic asthma mice, and to explore its immune regulatory mechanism, especially on mast cell (MC) degranulation. The results showed TMDCD could not only reduce the airway hyperresponsiveness (AHR), inflammatory cell infiltration and mucus secretion in the lung tissue of OVA challenged mice, but also decrease the levels of total IgE, OVA-specific IgE, histamine and LTC4 in serum. We found that TMDCD can downregulate the expression of Fractalkine, Tryptase ε, IL-25, CCL19, MCP-1, OX40L, Axl, CCL22, CD30, G-CSF, E-selectin, OPN, CCL5, P-selectin, Gas6, TSLP in OVA challenged mice serum by using mouse cytokines antibody array. It has been reported in some literatures that these differentially expressed proteins are related to the occurrence of allergic asthma, such as tryptase ε, MCP-1, CCL5, etc. can be released by MC. And the results of in vitro experiments showed that TMDCD inhibited the degranulation of RBL-2H3 cells stimulated by DNP-IgE/BSA. Taken together, we made the conclusion that TMDCD could reduce the infiltration of inflammatory cells in lung tissue and alleviate airway remodeling in mice with allergic asthma, showed the effects of anti-inflammatory and antiasthmatic. TMDCD could also reduce the levels of IgE, histamine, LTC4, Tryptase ε, and other MC related proteins in the serum of allergic asthma mice, and the in vitro experiments showed that TMDCD could inhibit IgE mediated degranulation and histamine release of RBL-2H3 cells, proved its anti allergic effect.